Congestive heart failure (Timonium, Md. : Milner-Fenwick, 1993)
It discusses the anatomy and physiology of the heart, left heart failure, right heart failure, immediate treatment and care, continued care and treatment , and rehabilitation of the patient
Copy available in DVD format
Keywords: Congestive heart failure -- Nursing